Albert Peter Low et l’exploration du Québec-Labrador - Caron, Fabien (Cahiers de géographie du Québec, 1965)
In 1890, the interior of the Québec-Labrador peninsula was still virtually unexplored. Ten years later, the blank on the map had been filled : geology, physio-graphy, climate, vegetation, fauna and inhabitants of the region were known, at least in their great lines, thanks to the remarkable amount of exploratory work done by the Canadian geologist A. P. Low. In thirteen seasons, Low sailed, canoed, dog-sledded and snowshoed some 10,000 miles in and around the peninsula. He gave the first accurate picture of the country, traced the outline of the Labrador Trough and gave the first description of the iron ores it contains. He surveyed the course of the principal rivers and a large portion of the northern and western coasts. His huge 1895 report is still considered the best work ever to have been printed about the region. Outside Québec-Labrador, Low worked in Gaspé, Manitoba, and was leader of the 1903-04 Canadian Arctic expedition on board the Neptune; on that occasion, he took formal possession of the Arctic Archipelago on behalf of Canada. Today's scientist, greatly helped by the airplane and modem technique, should be forever grateful to this indefatigable predecessor.